Biochemical Signals Mediate the Crosstalk between Cartilage and Bone in Osteoarthritis. (6th April 2020) - Zhou, Xuchang; Cao, Hong; Yuan, Yu; Wu, Wei
Abstract : Osteochondral junction is a functional unit comprising the articular cartilage, calcified cartilage, and subchondral bone. Alteration in any component of this composite unit can disrupt the joint integrity and function directly or indirectly. Biochemical signals mediate the crosstalk between tissues and play an essential role in the initiation and progression of osteoarthritis. As osteoarthritis progresses, abnormal subchondral bone remodelling leads to increased angiogenesis and porosity of the subchondral bone plate, which further triggers biochemical signals to mediate the crosstalk between cartilage and bone, contributing to the progression of osteoarthritis. Notably, common biochemical signals include the TGF- β /Smad, Wnt/ β -catenin, RANK/RANKL/OPG, and MAPK pathways. This biomarker crosstalk network is the basis of osteoarthritis pathogenesis, and some of their key regulators may be potential therapeutic targets for osteoarthritis drug therapy. This review summarised the biochemical crosstalk between cartilage and bone in the pathogenesis of osteoarthritis, which may provide the basis for the discovery of osteoarthritis treatment targets.